Cytogenetic studies in some representatives of the subfamily Pooideae (Poaceae) in South Africa. 3. The tribe Poeae - J. J. Spies; S. M. C. van Wyk; I. C. Nieman; E. J. L. Liebenberg (Bothalia: African Biodiversity & Conservation, 1997)
This is a report on chromosome numbers for the tribe Poeae, which is represented in South Africa mainly by naturalized exotics. Chromosome numbers of 67 specimens, representing 26 species and 11 genera, are presented. These numbers include the first reports on Poa binata Nees (n = 3x = 21 and n = 4x = 28), Puccinellia acroxantha C.A.Sm. & CE.Hubb. (n = 3x = 21) and P. angusta (Nees) C.A.Sm. & C.E.Hubb. (n = x = 7). New ploidy levels are reported for Catapodium rigidum (L.) CE.Hubb. (n = 2x = 14), Festuca caprina Nees (n = 2x = 14) and F. scabra Vahl (n = x = 7).